Risk for morbidity and mortality after neurosurgery in older patients with high grade gliomas – a retrospective population based study - David Löfgren; Antonios Valachis; Magnus Olivecrona (BMC Geriatrics, 2022)
Abstract Background Although high grade gliomas largely affect older patients, current evidence on neurosurgical complications is mostly based on studies including younger study populations. We aimed to investigate the risk for postoperative complications after neurosurgery in a population-based cohort of older patients with high grade gliomas, and explore changes over time. Methods In this retrospective study we have used data from the Swedish Brain Tumour Registry and included patients in Sweden age 65 years or older, with surgery 1999–2017 for high grade gliomas. We analysed number of surgical procedures per year and which factors contribute to postoperative morbidity and mortality. Results The study included 1998 surgical interventions from an area representing 60% of the Swedish population. Over time, there was an increase in surgical interventions in relation to the age specific population (p < 0.001). Postoperative morbidity for 2006–2017 was 24%. Resection and not having a multifocal tumour were associated with higher risk for postoperative morbidity. Postoperative mortality for the same period was 5%. Increased age, biopsy, and poor performance status was associated with higher risk for postoperative mortality. Conclusions This study shows an increase in surgical interventions over time, probably representing a more active treatment approach. The relatively low postoperative morbidity- and mortality-rates suggests that surgery in older patients with suspected high grade gliomas can be a feasible option. However, caution is advised in patients with poor performance status where the possible surgical intervention would be a biopsy only. Further, this study underlines the need for more standardised methods of reporting neurosurgical complications.